Said Nursi’s Perspective of Islamic Spirituality - Çaksen, Hüseyin; Hussain, Khalid; Salih Yahya Inan, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2026)
This article re-examines the concepts of “religion” and “spirituality” within an Islamic framework by situating them in contemporary academic discussions and in selected writings of Said Nursi. While Islamic scholarship traditionally treats spirituality as an inner dimension of din, modern disciplinary approaches to religion have reshaped how these terms are analysed and compared. Drawing on recent scholarship in religious studies, anthropology, and Sufi thought, this study clarifies the terms and explores their interrelationship in light of Islamic metaphysics, Qurʾānic ethics, and the spiritual psychology found in Nursi’s Risale-i Nur. The article argues that although religion and spirituality are sometimes treated as distinct domains in modern discourse, Islamic intellectual traditions view them as mutually constitutive, with spirituality functioning as the interior realization of the divine guidance articulated through revelation, law, and prophetic teachings. The study concludes that a comprehensive understanding of spirituality within Islam requires acknowledging its rootedness in the broader structures of din, its historical expressions, and its ongoing reinterpretation in modern Muslim thought.